Penilaian keragaman beberapa karakter pertumbuhan koleksi plasma nutfah bibit kina (Cinchona ledgeriana Moens) secara destruktif - Dian Hidayat; Liberty Chaidir; Heri Syahrian; Noladhi Wicaksana (Jurnal Penelitian Teh dan Kina, 2018)
Selecting Ledgeriana cutting in the nursery has aimed to obtained cinchona superior clones. Cuttings Ledgeriana is one alternative technique to propagate cinchona plant to overcome the incompatibility in the grafting technique. The information about plant variability needs to be known to determine the effectiveness of the selection process. This study aims to determine the value of growth component variability of potential cinchona clones from ledger cutting nursery. The research was conducted at the Research Institute for Tea and Cinchona from November 2017 to July 2018. The experiment used a Randomized Block Design (RBD) with 17 Cinchona Ledgeriana clones, consisting of 16 BTG clones and clone Cib 5 as a control. The results of the analysis showed that all components observed were categorizing as the narrow variability so that no clones were entered in the selection criteria.